(untitled) (Rivista Italiana di Filosofia Analitica Junior, 2014)
ABSTRACT A relevant part of the literature about the metaphysical problem of persistence of concrete particulars exhibits, I believe, too much freedom as far as the use of terms like “Four-Dimensionalism”, “Perdurantism” and “Doctrine of temporal parts” is concerned. This attitude clashes against the rigorous and valid arguments of many four-dimensionalist views and it is mainly due to a lack of precision on the four-dimensionalist side. In this work I analyse Parsons’ (2000) attempt to clarify the content of these notions. His clarification, based on the postulation of a difference between temporal parts and temporal extent, is aimed at demonstrating that Four-Dimensionalism and Perdurantism have not the same content and are not tied by any apriori connection. I endorse Parsons’ clarification as legitimate from a logical and semantic point of view, but I maintain that, despite his useful distinction between Perdurantism as a theory of persistence and Four-Dimensionalism as a theory of extension, these doctrines are ultimately equivalent, when it comes to formulating a general view about material objects. Indeed, I argue that objects extended four-dimensionally necessarily persist by perduring, and perduring objects necessarily extend four-dimensionally in space-time.